2008
DOI: 10.2337/db07-0739
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Epidermal Growth Factor Receptor Phosphorylation Induces Resistance Artery Dysfunction in Diabetic db/db Mice

Abstract: OBJECTIVE-We previously showed epidermal growth factor receptor (EGFR) transactivation to be key mechanism in the regulation of resistance artery myogenic tone. Type 2 diabetes is associated with microvascular complications. We hypothesized that elevated EGFR phosphorylation contributes to resistance artery dysfunction in type 2 diabetes. RESEARCH DESIGN AND METHODS AND RESULTS-Diabetic db/db and nondiabetic (control) mice were treated with EGFR inhibitor (AG1478; 10 mg ⅐ kg Ϫ1 ⅐ day Ϫ1 ) for 2 weeks. Isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 36 publications
6
99
1
1
Order By: Relevance
“…In a recent study, using telemetry, we have shown that db/db mice are normotensive. 38 Blood pressure was normal and similar in all groups indicating that type 2 diabetic mice are not hypertensive. Our data are not in agreement with the Bagi et al study showing an increase of systolic blood pressure in diabetic mice.…”
Section: Discussionmentioning
confidence: 89%
“…In a recent study, using telemetry, we have shown that db/db mice are normotensive. 38 Blood pressure was normal and similar in all groups indicating that type 2 diabetic mice are not hypertensive. Our data are not in agreement with the Bagi et al study showing an increase of systolic blood pressure in diabetic mice.…”
Section: Discussionmentioning
confidence: 89%
“…Administration of AG1478 increased the rate of nerve damage from 40% to 80% at 10.5 mo. Although AG1478 is an effective EGFR inhibitor in vivo (78,79), as with many kinase inhibitors, off-target and systemic effects are possible. AG1478 is less effective in inhibiting other inflammation-related kinases (80).…”
Section: Discussionmentioning
confidence: 99%
“…The vessels were pressurized to 50 mmHg using pressureservo control perfusion system (Living Systems Instruments, St. Albans, VT) for a 40-min equilibration period. The vessel diameter was monitored by a video image analyzer as previously described (9,12).…”
Section: General Protocol In Micementioning
confidence: 99%